Reproductive Performance, Piglet Mortality and Reproductive Health Problems of Sows in The Ejisu Municipality - Joseph Atawalna; Essel Daniel Cobbinah Junior; Theophilus Nda Ennu (The International Journal of Tropical Veterinary and Biomedical Research, 2021)
A cross-sectional study was conducted among commercial pig farmers in the Ejisu Municipality to investigate reproductive performance, piglet mortality, and reproductive health problems on their farms. Questionnaires designed to obtain information on reproductive performance and reproductive health problems were administered to a total of 50 randomly selected pig farmers. Three farms were randomly selected to monitor farrowing and pre-weaning piglet mortality. The farrowing records of a minimum of 10 sows on each farm were taken, and the piglets followed up to the point of weaning by six weeks. Records of piglet mortalities and their causes were retrieved from farm records or post mortem reports. The mean litter size, stillbirth per litter, piglet birth weight (Kg), weaning to estrus interval, and gestation period were 9.5± 1.4, 1.6 ± 0.2, 1.0 ± 0.1, .7±1.0 days, and 115.1± 2.6 days, respectively. The pre-weaning mortality (%) at day 42 was 18.7 and ranged from 7.3-28.3. Within the first two days post farrowing, mechanical crushing (8.9%) of piglets by sows and piglet starvation (7.2%), while diarrhea (2.5%) and piglet anemia (1.5%) accounted for mortalities within the first two weeks of life. Reproductive health problems by frequency of occurrence included mastitis (23%), agalactia (18%), stillbirths (18%), repeat breeders (14%) and dystocia (14%). The study concluded that the reproductive performance of sows was satisfactory, while pre-weaning piglet mortality was high. It is recommended to intensify extension education on the management of piglets after farrowing.